Modules with Unique Closure Relative to a Torsion Theory. III - Doğruöz, S.; Harmanci, A.; Smith, P. F. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We continue the study of modules over a general ring R whose submodules have a unique closure relative to a hereditary torsion theory on Mod-R. It is proved that, for a given ring R and a hereditary torsion theory τ on Mod-R, every submodule of every right R-module has a unique closure with respect to τ if and only if τ is generated by projective simple right R-modules. In particular, a ring R is a right Kasch ring if and only if every submodule of every right R-module has a unique closure with respect to the Lambek torsion theory.